Can tolvaptan usage cause cytotoxicity? An in vitro study - Erdem Tunçdemir, Beril (The European Research Journal, 2023)
Objectives: Tolvaptan is a nonpeptide V2 (vasopressin) receptor antagonist which is commonly used for treatment of hypernatremia. Besides it is mostly used for rescue strategies of mutant V2 receptors which are responsible for congenital type of Nephrogenic Diabetes insipidus (NDI) as a pharmacological chaperone (PC) treatment. Tolvaptan is metabolized by CYP3A4 and usage of tolvaptan may cause cytotoxicity which can be prevented by antioxidants. The aim of this study is investigating cytotoxic effect of tolvaptan on COS-1 cells and preventing it via antioxidants such as Vitamin C and N-acetyl cysteine (NAC). Methods: To measure cytotoxicity of tolvaptan, COS-1 cells were separated in three groups; tolvaptan, tolvaptan+Vitamin C and tolvaptan+NAC. 24 h after cells were seeded in 96-well plates, they were treated with different concentrations of tolvaptan, tolvaptan+Vitamin C and tolvaptan+NAC. After 24 h incubation, the (3-(4,5-Dimethylthiazol- 2-yl)-2,5-diphenyltetrazolium bromide) [MTT] analysis were performed and GraphPad Prism 5.01 for Windows was used for statistical analysis. Results: According to results of MTT assay, treatment with tolvaptan did not decrease cell viability except that treatment of 10-5 M tolvaptan showed significantly decrase on cell viability compared to control group. At the concentration of 10-9 M, there was significantly different cell viability between treated with tolvaptan and tolvaptan+Vitamin C. Conclusions: Tolvaptan may show its cytotoxic effects when it is used for the treatment of hyponatremia than its usage of as a PC. Since low concentrations of tolvaptan for a short time treatment is enough for its PC role, it may not show any cytotoxic effect on cells which is coherent with our results.